Courtesy stigma among primary caregivers of children with autism spectrum disorder in eastern China - Chen, Xu; Tong, Jiao; Jiang, Bochen; Ma, Shan; Wang, Xin; Sun, Xun; Liu, Yuan; Yan, Dongmei; Wang, Leilei (Frontiers in Psychiatry, 2023)
Introduction: The experience and perception of stigma is a common problem among primary caregivers of children with autism spectrum disorder (ASD), and has a profound adverse impact on primary caregivers and children with ASD; however, few studies have explored courtesy stigma among primary caregivers of children with ASD in the Chinese context. The aim of this study was to explore the status of courtesy stigma among primary caregivers of children with ASD in Lianyungang, Jiangsu Province, Eastern China, and to conduct in-depth analysis of its predictors from multiple perspectives. Methods: An institution-based multi-center cross-sectional survey was conducted in the rehabilitation department of a large specialized hospital and 10 rehabilitation centers for children with special needs in Lianyungang, Jiangsu Province, Eastern China, from October 2022 to February 2023. A structured questionnaire to assess child-related factors, primary caregiver-related factors, courtesy stigma, general self-efficacy, and social support, was used to collect data. Predictors of courtesy stigma among primary caregivers of children with ASD were identified by linear regression. Results: A total of 428 primary caregivers of children with ASD were recruited. The mean ± standard deviation (SD) score for courtesy stigma was 7.49 ± 4.13. Multiple linear regression analysis revealed that primary caregivers of children with ASD who were not too satisfied with their current marital status (β = 1.21, 95% CI: 0.34–2.08, P < 0.05) were more likely to have a high courtesy stigma; however, significantly lower courtesy stigma was observed in primary caregivers of children with ASD who were not picky eaters (β = –1.33, 95% CI: –2.08– –0.58, P < 0.05), and who reported low level challenge in caring for children with ASD (β = –1.16, 95% CI: –2.20– –0.12, P < 0.05), good general self-efficacy (β = –0.16, 95% CI: –0.25– –0.06, P < 0.05), and good social support (β = –0.04, 95% CI: –0.08– –0.01, P < 0.05). Conclusion: There is a high level of courtesy stigma among primary caregivers of children with ASD in eastern China, and it is affected by numerous factors. More resources should be directed to groups that are more likely to experience stigma.